Redesain Bendung Semat Kali Gawe Kabupaten Jepara 2025 - Dwi Ahamad Maulana; Muhammad Dwi Dany Sadewa; Sofyan Anas; Devandaru Maulana; Muhammad Tafrihan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study evaluates the retrofit design of the Semat weir on the Kali Gawe in Jepara Regency. The retrofit aims to adjust the weir’s hydraulic capacity to accommodate estimated flood discharges while ensuring the structure’s stability under applied loads. In the agricultural context, adequate water availability for irrigation directly affects crop yields; conversely, the rainy season often increases river flow and flood risk. Irrigation structures such as weirs are therefore required to raise river water levels to divert flow into irrigation channels and to regulate water distribution. Flood discharge estimates were derived from precipitation data and watershed (drainage basin) characteristics. Flood hydrograph planning is a critical design step for the weir. Log-Pearson Type III analysis was used to determine probable precipitation values for several recurrence intervals. Those design precipitation values were then converted into design flood discharges using synthetic unit hydrograph methods, specifically the Snyder, Nakayasu, and Gamma HSS approaches. Employing the Gamma synthetic unit hydrograph for the 50-year return period (Q50) produced a design flood discharge of 2,536.52 m³/s for that recurrence interval. Structural stability analyses of the redesigned weir indicate safety factors well above customary thresholds: overturning resistance factor = 11.6 (required ≥ 1.5), sliding resistance factor = 4.80 (required ≥ 2.0), and piping (internal erosion) factor = infinite (required ≥ 4). All evaluated stability parameters therefore satisfy standard safety criteria.